Knowledge, perceptions, and consumption behaviour of cosmetics among undergraduates of Sri Lanka: a descriptive cross-sectional study - Udayanga, Lahiru; Subashini, Nirma; Udugama, Menuka; Silva, Prabha; Ranathunge, Tharaka (Frontiers in Public Health, 2024)
Background: Despite the increasing usage of personal care products among young adolescents in Sri Lanka, limited studies have been conducted to understand the behaviour of cosmetic users and associated health complications. Therefore, the current study was conducted to evaluate the cosmetic consumption related behaviours of the undergraduate community in Sri Lanka and to identify the driving factors behind the incidences of cosmetic related adverse health effects. Method: An analytical cross-sectional study was conducted by recruiting 421 undergraduates from five state universities in Sri Lanka through stratified random sampling, as the study population. Information on socio-demographic factors and cosmetic consumption behaviour of the participants were acquired through a self-administrated structured questionnaire, along with Knowledge, Attitudes and Practices (KAP) relevant for cosmetic usage. The Binary Logistic Regression model was used to determine the significant socio-demographic driving factors on cosmetic usage among the undergraduate community in Sri Lanka at a confidence level of 95% Intervals. Results: Around 96.4% of the study population used one or more cosmetic products (77%) out of which, 75.3% experienced cosmetic related adverse health effects. Skin dryness (24%), acne (21%), allergies (20.5%) and rashes (19.8%), were identified as the most dominant adverse health effects, related to cosmetic usage. Perfumes (65.6%), face cream (63.2%) and body lotion/hand cream (60.6%), were the mostly used cosmetic products. Around 47.5% were characterized with a low level of knowledge on cosmetics. Gender, academic year, knowledge on cosmetics, monthly expenditure on cosmetics, source of recommendation for cosmetics, practices related to purchase and consumption of cosmetics and preference to receive medical care in case of cosmetic related emergency were recognized as significant risk factors (P<0.05) associated with the incidence of cosmetic related adverse health effects among undergraduate students. Conclusion: Given the high prevalence of cosmetic related adverse health effects, the health authorities of Sri Lanka should pay more attention towards the wellbeing and responsible cosmetic usage among undergraduates. Designing of effective tools and regulations to monitor the cosmetic market and improving the knowledge on cosmetics are recommended to ensure safe cosmetic usage within the country in general and of adolescent users in particular.